Analisis Penggunaan Kapur Tohor (CAO) Untuk Pengelolaan Air Asam Tambang di Pt Lematang Coal Lestari (LCL) Gunung Raja Muara Enim - Sari, Maresta; Gumanti, Suhardiman; Susilo, Aris (PT. Publikasiku Academic Solution, 2025)
The occurrence of mine acid water cannot be left unchecked because it has a negative impact on the surrounding community and the environment, both directly and indirectly. Therefore, the prevention and management of mine acid water is carried out by settling and neutralizing mine acid water using Lime and Chemical Cationic Coagulant. The purpose of this study is to find out the process of mining acid water management using the active method used at PT LCL. The result of this study is to determine the stages of mining acid water management starting from AAT pumping, chemical cationic coagulant, inlet channel pH measurement, inlet channel liming, checking the color and pH of outlet channel water if needed, as well as sedimentation, and then if the pH is in accordance with the environmental quality standards, mine acid water can be flowed to the receiving water body of the Penimir River. The dosage of lime and Chemical Cationic Coagulant used varies, according to the condition of the water in the KPL. If the pH of the water decreases, it will be sprinkled with lime, if the water is cloudy, chemical cationic coagulant will be sprinkled for precipitation. The pH of the water discharged into the river is already pH 6.